The Effect of Supervision and Communication on Employee Performance at PT Jamkrindo Makassar Branch - Mursidah (International Publisher, 2024)
This study aims to determine whether supervision and communication affect employee performance at PT Jamkrindo Makassar Branch. Data collection uses primary and secondary data obtained by distributing questionnaires using saturated sampling techniques. The population is all employees in the office of PT Jamkrindo Branch Makassar, namely as many as 37 employees and this number is also used as a sample. The results of this study were tested by instruments in the form of validity and reliability tests as well as classical assumption tests in the form of assumptions of normality, multicollinearity and heteroscedasticity. Methods of data analysis using multiple linear regression techniques. The results of the study show that the partial hypothesis indicates that the variable of supervision has no effect on employee performance and communication has a positive and significant effect on employee performance then simultaneously the variables of supervision and communication have a positive and significant effect on employee performance.